INTERRELATION OF CARDIOVASCULA RISK FACTORS WITH AN INDEX OF THE KLINIKO-METABOLIC STATUS IN WOMEN WITH TYPE 2 DIABETES - Alieva, T.T. (World of Medicine and Biology, 2010)
Тhe relation between the dynamic changes of index of clinical-metabolic status (IKMS) and all parameters it included during therapy in 28 males with type 2 DM has been spent. Results: in majority IKMS depends on the level of arterial blood pressure. Also we investigated the BMI, HbA1c and aterogen index MM. Arterial blood pressure, HbA1c and aterogen index MM exert main effect on IKMS during therapy. The same time the BMI express a non significant effect on this index, as normalization of bode weight requires a long time other parameters.